A MutSβ-Dependent Contribution of MutSα to Repeat Expansions in Fragile X Premutation Mice? - Xiao-Nan Zhao; Rachel Lokanga; Kimaada Allette; Inbal Gazy; Di Wu; Karen Usdin (PLoS Genetics)
The fragile X-related disorders result from expansion of a CGG/CCG microsatellite in the 5' UTR of the FMR1 gene. We have previously demonstrated that the MSH2/MSH3 complex, MutSβ, that is important for mismatch repair, is essential for almost all expansions in a mouse model of these disorders. Here we show that the MSH2/MSH6 complex, MutSα also contributes to the production of both germ line and somatic expansions as evidenced by the reduction in the number of expansions observed in Msh6-/- mice. This effect is not mediated via an indirect effect of the loss of MSH6 on the level of MSH3. However, since MutSβ is required for 98% of germ line expansions and almost all somatic ones, MutSα is apparently not able to efficiently substitute for MutSβ in the expansion process. Using purified human proteins we demonstrate that MutSα, like MutSβ, binds to substrates with loop-outs of the repeats and increases the thermal stability of the structures that they form. We also show that MutSα facilitates binding of MutSβ to these loop-outs. These data suggest possible models for the contribution of MutSα to repeat expansion. In addition, we show that unlike MutSβ, MutSα may also act to protect against repeat contractions in the Fmr1 gene.